Oscillatory neuronal dynamics associated with manual acupuncture: a magnetoencephalography study using beamforming analysis - Asghar, Aziz; Johnson, Robyn; Woods, William; Green, Gary G.; Lewith, George; MacPherson, Hugh (Frontiers in Human Neuroscience, 2012)
Magnetoencephalography (MEG) enables non-invasive recording of neuronal activity, with reconstruction methods providing estimates of underlying brain source locations and oscillatory dynamics from externally recorded neuromagnetic fields. The aim of our study was to use MEG to determine the effect of manual acupuncture on neuronal oscillatory dynamics. A major problem in MEG investigations of manual acupuncture is the absence of onset times for each needle manipulation. Given that beamforming (spatial filtering) analysis is not dependent upon stimulus-driven responses being phase-locked to stimulus onset, we postulated that beamforming could reveal source locations and induced changes in neuronal activity during manual acupuncture. In a beamformer analysis, a two-minute period of manual acupuncture needle manipulation delivered to the ipsilateral right LI-4 (Hegu) acupoint was contrasted with a two-minute baseline period. We considered oscillatory power changes in the theta (4-8Hz), alpha (8-13Hz), beta (13-30Hz) and gamma (30-100Hz) frequency bands. We found significant decreases in beta band power in the contralateral primary somatosensory cortex and superior frontal gyrus. In the ipsilateral cerebral hemisphere, we found significant power decreases in beta and gamma frequency bands in only the superior frontal gyrus. No significant power modulations were found in theta and alpha bands. Our results indicate that beamforming is a useful analytical tool to reconstruct underlying neuronal activity associated with manual acupuncture. Our main finding was of beta power decreases in primary somatosensory cortex and superior frontal gyrus, which opens up a line of future investigation regarding whether this contributes towards an underlying mechanism of acupuncture.